Ever [compact disc, unabridged] - Levine, Gail Carson (Levine, Gail Carson. Ella enchanted., 2008)
Fourteen-year-old Kezi and Olus, Akkan god of the winds, fall in love and together try to change her fate--to be sacrificed to a Hyte god because of a rash promise her father made--through a series of quests that might make her immortal.